HUBUNGAN PENGETAHUAN, SIKAP DAN TINDAKAN MASYARAKAT DALAM PENGGUNAAN JAMBAN SEHAT TERHADAP KASUS DIARE PUSKESMAS EDISON JAAR KECAMATAN DUSUN TIMUR KABUPATEN BARITO TIMUR KALIMANTAN TENGAH. - Puji Astuti; Emmy Sri Mahreda; Rizmi Yunita; Irma Febrianty (EnviroScienteae, 2021)
The disposal of human feces must be properly managed to prevent environmental pollution, which is usually done in latrines or toilets. The achievement of using semi-permanent healthy latrines (simple rural) in 2018 was 80% in the Edison Jaar health center work area, which covers 6 (six) villages. Data on 300 cases of diarrhea exceeded the target estimate of 279 cases of diarrhea disease while In 2019, the community had 100% access to healthy latrines, with building types meeting national health standards, only 103 (5%), 1923 others (95%) were constructed with rural simple latrines which were still at high risk of contaminating feces into groundwater flows. The number of cases of diarrheal disease increased to 328 cases. Methods:This type of research is analytical descriptive, using the Spearman correlation analysis method and  mixed methods data collection.The sample is 77 people with diarrhea who have new toilets or their location around the river. The research instrument used a questionnaire. The results showed that  the action variable has a high / strong level of closeness ( r=0.623 p=0.0000001, 95%CI). There is a close relationship actions of the community in using healthy latrines on diarrhea cases  in the Edison JaarHealth Center Work Area.Abstract: The disposal of human feces must be properly managed to prevent environmental pollution, which is usually done in latrines or toilets. The achievement of using semi-permanent healthy latrines (simple rural) in 2018 was 80% in the Edison Jaar health center work area, which covers 6 (six) villages. Data on 300 cases of diarrhea exceeded the target estimate of 279 cases of diarrhea disease while In 2019, the community had 100% access to healthy latrines, with building types meeting national health standards, only 103 (5%), 1923 others (95%) were constructed with rural simple latrines which were still at high risk of contaminating feces into groundwater flows. The number of cases of diarrheal disease increased to 328 cases. Methods:This type of research is analytical descriptive, using the Spearman correlation analysis method and  mixed methods data collection.The sample is 77 people with diarrhea who have new toilets or their location around the river. The research instrument used a questionnaire. The results showed that  the action variable has a high / strong level of closeness ( r=0.623 p=0.0000001, 95%CI). There is a close relationship actions of the community in using healthy latrines on diarrhea cases  in the Edison JaarHealth Center Work Area.